Структурно-полевой подход к синтаксической фразеологии русского языка. Часть 2 - Pavlova, Anna (Przegląd Wschodnioeuropejski, 2023)
The paper deals with the problems of the structural field approach to the study of linguistic phenomena. The foundations for building a field theory in the grammatical structure of language were laid by V. G. Admoni in his works on the theoretical grammar of German. Effectively, the same approach can be applied to any language phenomena as it has a number of advantages over classifications involving the distribution of objects in the systems of level hierarchy. This paper demonstrates the advantages of the structural field approach and possibilities. The author’s aim is to study the field of syntactic phraseological phenomena (phraseme constructions), identifying its core, centre, periphery, and adjacent fields, as well as describing the advantages of this method of studying linguistic phenomena. Phraseme constructions belong to the linguistic system and occupy an important place in the grammar of constructions. They are constantly reproduced and filled in speech with concrete vocabulary, stable syntactic models retrieved from memory not elementally, but entirely, and having idiomatic character (the meaning of the filled model cannot be deduced if one does not know the structure of the model and its meaning even before any filling). The properties, namely: polyelementality, reproducibility, stable syntactic structure, idiomaticity and fillability in speech, are indispensable characteristics of the phenomenon described herein: deprived of at least one of them, a phraseological construction ceases to be one. However, phraseme constructions have a larger, typical set of characteristics. In this paper, they are considered from the perspective of an increase and decrease in these characteristics, which allows us to study phraseological constructions as a field whose structure is determined by multiple axes. The structural field approach frees scholars from the need to make clear distinctions between linguistic phenomena with similar functionality on different levels if they have several, divergent typical, basic features of its concrete application through the example of the field of syntactic phraseology.